ANATOMI DAN KUALITAS SERAT KAYU UTAP-UTAP (Aromadendron elegans Bl.) DAN TUJUH JENIS KAYU KURANG DIKENAL LAINNYA - Y l Mandang; Sissi Artistien (Jurnal Penelitian Hasil Hutan, 2003)
Gross and anatomical features of Aromadendron  elegans and seven lesser known wood species were observed and described for identification purposes and for evaluation of their suitable uses. Fiber dimension were also measured to evaluate their possible uses for pulp and paper. Several important features for identification were detected: 1) oil cells and closely spaced parenchyma bands in Aromadendron elegans; 2) wood semi-ring porous in Melia  dubia; 3) radial intercellular canal and septate fibers  in  Lannea coromandelica; 4) ray storied and druses crystals in Hibiscus tiliaceus; 5) ray very high and contain sheath cells in Baccaurea sp.; 6) ray homocellular uniseriate and included phloem in Dolichandrone  spathacea ; 7)  parenchyma  aliform and confluent, prismatic crystals in chambered axial parenchyma of  Acrocarpus  fraxinifolius; 8)  wood  white, fibers with distinctly bordered pit, and prismatic crystals in chambered axial parenchyma of  Flindersia  australis. All wood species  studied  have density and  considerable strength  to  be  used for construction  purposes. Aromadendron elegans,  Melia  dubia,  and  Flindersia australis have decorative appearance so they are suitable for furniture.  Flindersia australis is white and  has moderately fine  texture so it could be usedfor  "ram in"  substitute.   Fibers quality of all species studied belongs to quality class II. The total of fibers dimension derived values, of Aromadendron elegans, Melia   dubia, Flindersia  australis  and Dolichandrone  spathacea  are  the highest  among  eight  wood species studied; further studies  on pulping characteristics  are therefore recommended for these wood species.